2018
DOI: 10.1111/1475-6765.12311
|View full text |Cite
|
Sign up to set email alerts
|

Economic grievances and political protest

Abstract: How do economic grievances affect citizens’ inclination to protest? Given rising levels of inequality and widespread economic hardship in the aftermath of the Great Recession, this question is crucial for political science: if adverse economic conditions depress citizens’ engagement, as many contributions have argued, then the economic crisis may well feed into a crisis of democracy. However, the existing research on the link between economic grievances and political participation remains empirically inconclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…Evidence from a longstanding literature on relative deprivation shows that discrepancies between expectations and reality have political consequences (e.g., Burgoon et al 2019; Geschwender 1964; Gurr 1970; Kurer et al 2019; Mitrea, Mühlböck, and Warmuth 2021; Paskov, Präg, and Richards 2021). Building on these insights, we propose that the discrepancies resulting from declining occupational mobility affect political behavior because those experiencing negative status discordance feel they have been denied the opportunity to secure the status they had come to expect for themselves based on standards set in childhood—expectations also encouraged by the postwar political consensus.…”
Section: The Politics Of Expectationsmentioning
confidence: 99%
“…Evidence from a longstanding literature on relative deprivation shows that discrepancies between expectations and reality have political consequences (e.g., Burgoon et al 2019; Geschwender 1964; Gurr 1970; Kurer et al 2019; Mitrea, Mühlböck, and Warmuth 2021; Paskov, Präg, and Richards 2021). Building on these insights, we propose that the discrepancies resulting from declining occupational mobility affect political behavior because those experiencing negative status discordance feel they have been denied the opportunity to secure the status they had come to expect for themselves based on standards set in childhood—expectations also encouraged by the postwar political consensus.…”
Section: The Politics Of Expectationsmentioning
confidence: 99%
“…Scholars have argued that people are more likely to participate in contentious political action when they are dissatisfied with the economic or political situation; when they are aggrieved (Davies 1962;Gurr 1970). While grievance-based explanations of protest have been discarded for some time, recent contributions have revived their importance and showed that people who feel left behind or dissatisfied with their economic situation turn to the streets to voice frustrations (Grasso and Giugni 2016;Kern, Marien, and Hooghe 2015;Kurer et al 2019). This is not only the case in advanced economies, but also applies to less developed contexts where the average protester has been shown to be driven by personal, economic dissatisfaction rather than political demands (Mueller 2018).…”
Section: International Trade and Political Protestmentioning
confidence: 99%
“…We concentrate on one dependent variable: whether a respondent indicated that s/he participated in a peaceful/lawful demonstration in the past 12 months. Using the protest item for recent participation reduces the potential of recall errors and measures more closely people's reaction to ongoing developments instead of their lifetime protest experience (Dodson 2015), which is why it has become the standard item used in the literature (Grasso and Giugni 2016;Kurer et al 2019).…”
Section: Individual Grievances and Protest Participationmentioning
confidence: 99%
“…Small samples impede running detailed analyses of, for instance, personal economic circumstances, and how they affect young people's relationship to the political system. More recent research has focused attention on the importance of distinguishing between, for instance, economic grievances and feelings of relative deprivation (both in comparison to others and in comparison to one's own situation over time; see Kurer et al 2018) among the factors that explain protest mobilization in Europe.…”
Section: Resultsmentioning
confidence: 99%
“…Lack of resources is likely to produce apathy while a change in resources is more likely to mobilize protest actions (Kurer et al 2018). In light of changes in economic and labour conditions across Europe, the distinction between level of resources on the one hand, and changes in the endowment of resources on the other, could be key to understanding what drives young people out into the streets.…”
Section: Resultsmentioning
confidence: 99%